(3CSS h eHGOF GdeMGSHI GdeGdjI (B:s (3GdLRA GdGhd (B/s - (3GdJcQjJj, GSeGYjd jMjs; (3GdJejej, GfJUGQ YHhO eQGO s; (3GdWYeI,YHO GdhgGH MHT s ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2010)
(3GdJYQja HYde GdeMGSHI , JMdjd GdYedjGJ GdeGdjI , JSLjd GdYedjGJ GdeGdjI aj GdefTBJ GdNOejI , GdJShjGJ GdLQOjI h EceGd GdOhQI GdeMGSHjI aj GdeTGQjY GdNOejI , GdeYGdLI GdeMGSHjI ddYedjGJ aj GdeTQhYGJ GdJLGQjI ,LQO GdeUQhaGJ h GdGjQGOGJ aj GdefTBJ GdJLGQjI , GdeNRhf GdSdYj (B/ (3GdLQO GdOhQj(B.s
(3GdcJGH eMce JMcjeG YdejG h efgLjG ; eQGLY U(B.307s
Keywords: (3GdeGdjIs; (3GdeMGSHIs; (3GdeMGSHI(B- (3GdeGdjIs